CD133 expression and the prognosis of colorectal cancer: a systematic review and meta-analysis. - Shicai Chen; Xinming Song; Zhihui Chen; Xinxin Li; Mingzhe Li; Haiying Liu; Jianchang Li (PLoS ONE)
Objective CD133 has recently been reported as a marker of cancer stem-like cells in colorectal cancer (CRC). However, its predictive value in CRC still remains controversial. In this study, we aimed to evaluate the association between the expression of CD133 and clinicopathological features and the outcome of CRC patients by performing a meta-analysis. Methods A comprehensive literature search for relevant studies published up to December 2012 was performed using PubMed, MEDLINE and ISI Web of Science. Only articles in which CD133 antigen was detected in situ localisation by immunohistochemical staining were included. This meta-analysis was done using RevMan 4.2 software. Results We found that a total of 15 studies involving 810 CD133-high and 1487 CD133-low patients met the inclusion criteria for the analysis of 5-year overall survival (OS) rate. In a random-effects model, the results showed that CD133-high expression in colorectal cancer was an independent prognostic marker correlating with both OS rate (RR = 0.67, 95%CI 0.54-0.82, P<0.01) and disease free survival (DFS) rate (RR = 0.71, 95%CI 0.52-0.96, P = 0.03). CD133-high expression was also associated with more T3,4 tumor invasion, N positive and vascular invasion cases, corresponding to a risk difference of 1.12 (95%CI 1.01-1.23, P = 0.03), 1.31 (95%CI 1.06-1.63, P = 0.01) and 1.24 (95%CI 1.08-1.41, P<0.01), respectively. However, when types of histology, lymphatic invasion and distant metastasis were considered, CD133 overexpression was not significantly related with these clinicopathological parameters. Conclusion Our meta-analysis results suggest that CD133 is an efficient prognostic factor in CRC. Higher CD133 expression is significantly associated with poorer clinical outcome and some clinicopathological factors such as T category, N category and vascular invasion in CRC patients.